2016
DOI: 10.1158/1055-9965.epi-15-0746
|View full text |Cite
|
Sign up to set email alerts
|

Variants in 6q25.1 Are Associated with Mammographic Density in Malaysian Chinese Women

Abstract: Background: Mammographic density is an established risk factor for breast cancer and has a strong heritable component. Genome-wide association studies (GWAS) for mammographic density conducted in women of European descent have identified several genetic associations, but none of the studies have been tested in Asians. We sought to investigate whether these genetic loci, and loci associated with breast cancer risk and breast size, are associated with mammographic density in an Asian cohort.Methods: We conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…9,31 Even though there are many studies of mammographic density of Chinese women, majority of these works explored Chinese women living in Western countries [32][33][34][35][36][37][38][39][40][41][42][43] or in Southeast Asia. 29,[44][45][46][47][48][49][50][51][52] To the best of our knowledge, only five papers were China-based work, 13,22,53,54 including one from Hong Kong Special Administrative Region. 55 Almost all of these five studies used women from local/city-level screening program or hospital-based data, three studies showed that age was negatively correlated with mammographic density, 13,22,53 and two of them reported a negative relationship for BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,31 Even though there are many studies of mammographic density of Chinese women, majority of these works explored Chinese women living in Western countries [32][33][34][35][36][37][38][39][40][41][42][43] or in Southeast Asia. 29,[44][45][46][47][48][49][50][51][52] To the best of our knowledge, only five papers were China-based work, 13,22,53,54 including one from Hong Kong Special Administrative Region. 55 Almost all of these five studies used women from local/city-level screening program or hospital-based data, three studies showed that age was negatively correlated with mammographic density, 13,22,53 and two of them reported a negative relationship for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are many studies of mammographic density of Chinese women, majority of these works explored Chinese women living in Western countries 32–43 or in Southeast Asia 29,44–52 . To the best of our knowledge, only five papers were China‐based work, 13,22,53,54 including one from Hong Kong Special Administrative Region 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated estrogen levels have been shown to be associated with an increased risk of breast cancer in previous studies [50]. It is hypothesized that rs2046210 together with ESR1 may play an essential role in estrogen-dependent mammary epithelial proliferation, which is associated with increased mammographic density and subsequent risk to BC [51][52][53]. Other loci, such as rs10474352 [54], rs6788895 [55], rs7107217 et al [56], were also identified in previous studies in HCW and have the potential to be a predictive variable to asses the risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…This differential effect is unexpected since estrogen signaling via ER is believed to increase the risk of ER-positive breast cancer and not have an effect on ER-negative breast cancer [54, 55]. However, ESR1 could also exert an effect via the stroma and many of the variants at this locus are known to affect mammographic density [2730] which is associated with both ER-positive and ER-negative breast cancer [56]. Furthermore, other genes at this locus including ARMT1, CCDC170 , and RMND1 may also be candidates for an effect on breast cancer risk [27, 5759].…”
Section: Discussionmentioning
confidence: 99%
“…Several GWAS studies have identified SNPs at 6q25 that are associated with breast cancer risk [13, 18, 20, 2327] and mammographic density [23, 2730]. The initial report identified a SNP in the intergenic region between ESR1 and CDCC170 in an East Asian population [24].…”
Section: Introductionmentioning
confidence: 99%